Effect of Fly Ash Height in the Adsorption Column to Remove Phosphate in Laundry Wastewater - Hafidya Norista Pramesti; Wisnu Setyabudi; Euis Nurul Hidayah; Okik Hendriyanto Cahyonugroho; Yayok Suryo Purnomo (Future Science)
Laundry wastewater is one of the contributors to domestic wastewater since laundry services have been increasing in urban living, especially in big cities. Laundry wastewater may contain phosphate compounds, and the concentration should be reduced before discharge into water bodies. One of the easiest and friendly methods for removing phosphate in laundry wastewater is by using the adsorption process. Adsorption is influenced by the adsorbent material, and fly ash has been implemented as adsorbent due to its high capacity to adsorb pollutants. This study aims to observe the effect of adsorbent height in the column and the effect of flow rate to treat phosphate in laundry wastewater. This study applied Thomas modeling to determine the model for fly ash capacity as adsorbent. The results showed that the highest flow rate, 15 mL/min, and the highest fly ash height 20 cm gave the optimum removal of phosphate, about 98.63-99.22%. Besides, Thomas model obtained the value of the linear regression coefficient of 0.5415.